RELATIONSHIP BETWEEN PRIMARY PRODUCTIVITY OF PHYTOPLANKTON AND NUTRIENTS IN COASTAL WATERS, PELINTUNG VILLAGE, MEDANG KAMPAI DUMAI DISTRICT - Pebriyanti, Salfiah; Badrun, Yeeri; Herlina, Nofripa (Asian Journal of Aquatic Sciences, 2023)
This study is to determine the relationship between primary productivity and nutrients in the coastal waters of Pelintung Village, Medang Kampai District, Dumai. The research was conducted in March 2022; the method used in this research is survey method and purposive sampling. The research location is divided into 3 station points namely tourist area, secondary vegetation forest area, and near industrial area. The results of the measurement of the highest primary productivity value are found at Station III which is 78.91 mgC/m2/hour which indicates mesotrophic water conditions, while the lowest primary productivity value is at Station II, which is 46.88 mgC/m2/hour which indicates oligotrophic water conditions. The results of the analysis of the concentration of nitrate and phosphate between stations also varied, namely for the nitrate value of 0.04 – 0.05 mg/L which was included in the less fertile category, while the phosphate concentration was 0.042 – 0.048 mg/L which was included in the fertile category in the waters. Furthermore, the relationship between nitrate concentration and primary productivity is a correlation coefficient value (r) = -0.070 which means that there is a weak relationship between nitrate concentration and primary productivity. Meanwhile, the relationship between phosphate concentration and primary productivity is the correlation coefficient (r) = 0.965, which means that there is a very strong relationship between phosphate concentration and primary productivity. So it can be concluded that nitrate and phosphate nutrients can affect the primary productivity of water.